2011
DOI: 10.1002/j.0022-0337.2011.75.1.tb05017.x
|View full text |Cite
|
Sign up to set email alerts
|

The Arizona Model: A New Paradigm for Dental Schools

Abstract: The traditional method for the delivery of didactic instruction and patient care in dental schools has come under ire from a number of sources over the past several years. The American Dental Education Association and others have outlined numerous issues impeding the swift progression of student learning through the dental curriculum. Declining state revenues allotted to dental education, the increasing shortage of dental faculty, and the management of student learning in an already overcrowded dental school c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…A sole study included a review of dentists’ self‐reported data about the non‐clinical information they solicited from older patients and their exposure to this population in dental school 23 . In two studies, performance on board exams was assessed 7 , 20 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sole study included a review of dentists’ self‐reported data about the non‐clinical information they solicited from older patients and their exposure to this population in dental school 23 . In two studies, performance on board exams was assessed 7 , 20 …”
Section: Resultsmentioning
confidence: 99%
“…Some dental schools have made important strides towards establishing CBDE goals, including mission statements and student competencies 6 , 7 . However, we were unable to find a comprehensive professional standard or matrix for CBDE that sets out the parameters of student readiness and methods to evaluate them.…”
mentioning
confidence: 93%
“…While numerous innovations have and are being implemented locally in the area of instruction, economic modeling, and assessment at the institutional level, three major systemic changes have been reported recently in dental education. The three innovations are the incorporation of new instructional models, 18 – 27 economic modeling, 16 and distributed/economic models that utilize community clinical training sites 28 . Additionally, external influence by regulatory‐related bodies has significantly impacted curricular modifications in dental schools.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Reflection connects recent cognition to the forgoing acquisition (Sobral DT, 2005) Reflective learners become critical thinkers, good professionals, (Koole et al, 2012) develop inter-personal/communication skills and case solving abilities and realize themselves, their beliefs and incentives deeply. (Kember et al, 2000) Traditional teaching/ learning strategies (Smith, Woldt, Cottam, & Cederberg, 2011;Vaugh L & Baker R, 2001) decrease students' learning motivation (Rashmi KA, 2012) therefore researchers of the nineteenth century (Sobral DT, 2000, 2001, 2005Schon, 1984 ;Kolb, 1984;Boud, Keogh, & Walker, 1985; ) created reflective writing that assisted them to mount Miller's pyramid from knowledge towards performance to build student's self-directed and lifelong learning capacities and heighten their motivation.…”
Section: Introductionmentioning
confidence: 99%